Notes on the diatom collection of the Natural History Museum, London (BM) II–IV. Some type specimens in the genus Aulacodiscus Ehrenberg and nomenclatural notes on Thumia Cleve ex F.B. Taylor - Williams, David M. (Phytotaxa, 2021)
The diatom collection at the Natural History Museum, London (BM) is in the process of reviewing the card index that is the primary guide. The cards direct the user to the glass slides in the collection that are supposed to include specimens of the particular species indicated. The cards indicate which slides contain type specimens. Not all the types have been discovered. Occasionally, a card will refer to a name that has never been published, effectively a manuscript or herbarium name. This series of notes has been created to clarify some of those names and, where necessary, validly publish the names (part I was published earlier, Williams 2020).